Physico-chemical properties and effects of chitosan-based accelerated portland cement on stem cells from human exfoliated deciduous teeth - Al-Ibrahim, Hasan Subhi Azeez (2021)
Advancement in the field of endodontic such as techniques, instrumentations and materials have considerably improved the oral health care and have made the dental treatment more efficient, as well as cost and time effective. Accelerated Portland cement (APC) is a potential material with favourable chemical, physical and biological properties. It was studied as an alternative material to overcome the major limitations of mineral trioxide aggregate (MTA) and portland cement (PC) such as delayed setting time and high cost of MTA. Chitosan (CT) has also been used in numerous medical applications due to its various biological properties. In this study, APC was prepared in combination with CT and designated as APC-CT. This study aimed to evaluate the chemical, physical and mechanical properties of APC-CT and to evaluate its biocompatibility, mineralization activity and dentinogenic/osteogenic differentiation potential on stem cells from human exfoliated deciduous teeth (SHED). APC-CT was prepared with various CT concentrations of 0.625%-, 1.25%- and 2.5%-CT solutions, and APC was used as control. The chemical characterizations by FTIR and FESEM/EDX were evaluated, in addition to the physical and mechanical properties such as setting time, compressive strength, surface microhardness, pH and solubility. Then, the effect of APC-CT on cell viability, attachment and apoptosis were assessed. The mineralization activity of SHED was evaluated by Alizarin Red staining and Von Kossa stain. Finally, the dentinogenic/osteogenic differentiation of SHED was analysed by evaluating the gene expression of selected dentinogenic/osteogenic markers i.e. DSPP, MEPE, DMP-1, OPN, OCN, OPG, RANKL, RUNX2, ALP and COL1A1 by real-time PCR. The results confirmed the interaction of CT with APC by FTIR spectra. The surface morphology of APC-CT was characterized by the presence of CT crystallites which spread and filled the spaces in APC structure that resulted in more homogeneous phases. The chemical compositions of APC and APC-CT were almost identical with intensified O, C and Si in APC-CT. The setting time, compressive strength, microhardness, pH and solubility obtained ranged between 46.6-48.5 min, 51.3-39.1 MPa, 44.89-38.57 HV, 11.04-11.02 (24 hrs) and 3.23-2.44%, respectively. CT improved the pH and solubility of APC and extended its setting times. However, compressive strengths were reduced and minimum effect on microhardness was observed. Cytotoxicity assays demonstrated that APC-CT supported the cell proliferation and interaction of SHED to the materials; as well as no apoptotic effect was observed. Alizarin Red and Von Kossa stainings demonstrated increased mineralization activity of SHED when treated with APC-CT. The expressions of DSPP, MEPE, DMP-1, OPN, OCN, OPG and RANKL markers were up-regulated in APC-CT-treated SHED. While, the expressions of RUNX2, ALP and COL1A1 markers were down-regulated. These findings demonstrate that APC-CT exhibits good chemical, physical and mechanical properties. APC-CT is non-toxic and promotes dentinogenic/osteogenic differentiation and mineralization activity; which provides potential applications of APC-CT in tooth/bone tissue engineering.